Enteral Linezolid as an Effective Option to Treat an Extremely Preterm Infant with Bacillus cereus Sepsis - Chiara Minotti; Luca Bonadies; Cecilia Liberati; Marica De Pieri; Carlo Giaquinto; Eugenio Baraldi; Daniele Donà (MDPI AG, 2022)
We report the safe and effective use of oral linezolid for treatment of Bacillus cereus sepsis in an extremely preterm neonate, previously fed with human donor milk, in which a Brevibacillus sp. was eventually found. Due to several predisposing factors, premature, very low birth weight newborns are extremely vulnerable to invasive infections by environmental pathogens. After vancomycin microbiologic treatment failure (despite adequate blood concentrations and clinical response), linezolid was chosen for its optimal enteral absorption and bioavailability, also after exhaustion of peripheral venous heritage. No adverse events were recorded, with clinical cure. We reviewed the literature on B. cereus infections in newborns, together with the available evidence on the use of linezolid in similar contexts.